The administration of criminal justice at the Cape of Good Hope 1795-1882. Volume One and Two - Fine, Hilton Basil (Institute of Criminology, 2023)
The purpose of this thesis is to examine the administration of criminal justice at the Cape of Good Hope during the crucial period 1795 - 1828 in order to provide an insight into the roots of our present system and to shed some light on the various factors which could play a role in the creation of a system of criminal justice.